USE OF THE INTERNET IN EDUCATIONAL AND TECHNOLOGICAL TRAINING OF STUDENTS (Pedagogy of Higher and Secondary Education, 2022)
In article Jeatures of use of a network the Interet in information technological preparation of pupils are clarified.
Keywords: Internet; information; server; provider